Peer-Mediated Multimodal Intervention Program for the Treatment of Children with ADHD in India: One-Year Followup. (20th December 2012) - Mehta, Sagar; Shah, Devesh; Shah, Kushal; Mehta, Sanjiv; Mehta, Neelam; Mehta, Vivek; Mehta, Vijay; Mehta, Vaishali; Motiwala, Smita; Mehta, Naina; Mehta, Devendra
Abstract : The objective was to assess the efficacy of a one-year, peer-mediated interventional program consisting of yoga, meditation and play therapy maintained by student volunteers in a school in India. The population consisted of 69 students between the ages of 6 and 11 years, previously identified as having attention deficit hyperactivity disorder (ADHD). A program, known as Climb-Up, was initially embedded in the school twice weekly. Local high school student volunteers were then trained to continue to implement the program weekly over the period of one year. Improvements in ADHD symptoms and academic performance were assessed using Vanderbilt questionnaires completed by both parents and teachers. The performance impairment scores for ADHD students assessed by teachers improved by 6 weeks and were sustained through 12 months in 46 (85%) of the enrolled students. The improvements in their Vanderbilt scores assessed by parents were also seen in 92% (P < 0.0001, Wilcoxon). The Climb-Up program resulted in remarkable improvements in the students' school performances that were sustained throughout the year. These results show promise for a cost-effective program that could easily be implemented in any school.